Ds0⁎±(2317) and KD scattering from Bs0 decay - Miguel Albaladejo; Marina Nielsen; Eulogio Oset (Physics Letters B, 2015)
We study the B¯s0→Ds−(KD)+ weak decay, and look at the KD invariant mass distribution, for which we use recent lattice QCD results for the KD interaction from where the Ds0⁎(2317) resonance appears as a KD bound state. Since there are not yet experimental data on this reaction, in a second step we propose an analysis method to obtain information on the Ds0⁎(2317) resonance from the future experimental KD mass distribution in this decay. For this purpose, we generate synthetic data taking a few points from our theoretical distribution, to which we add a 5% or 10% error. With this analysis method, we prove that one can obtain from these “data” the existence of a bound KD state, the KD scattering length and effective range, and most importantly, the KD probability in the wave function of the bound state obtained, which was found to be largely dominant in lattice QCD studies. This means that one can obtain information on the nature of the Ds0⁎+(2317) resonance from the implementation of this experiment, in the line of finding the structure of resonances, which is one of the main aims in hadron spectroscopy.